2016
DOI: 10.1007/s11356-016-7668-z
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of cardiovascular drugs in the sewage-impacted Vistula River and in tap water in the Warsaw region (Poland)

Abstract: In recent years, cardiovascular diseases were the second most common cause of death worldwide. Therefore, the consumption of drugs used to treat cardiovascular diseases is high. So far, there were no such comprehensive reports regarding the presence of cardiovascular drugs in surface and tap waters, particularly in Central and Eastern Europe. The aim of our study was to determine the presence of 30 pharmaceutically active compounds and some of their metabolites, at specific points of the Vistula River and in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…The stability of several ARA-II drugs, detected in polluted water resources, through the different stages involved in the production of drinking water has been previously reported (Giebułtowicz and Nałecz-Jawecki, 2016;Huerta-Fontela et al, 2011). Some data on the occurrence of sartans, and their primary biodegradation products at STPs (such as valsartan acid), in finished tap water have been also published (Giebułtowicz and Nałecz-Jawecki, 2016). However, no information is available neither regarding the variables affecting their half-lives (t1/2) during chemical treatments of polluted waters (as those employed in the production of tap water), nor above the possible formation of transformation products (TPs) during these processes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of several ARA-II drugs, detected in polluted water resources, through the different stages involved in the production of drinking water has been previously reported (Giebułtowicz and Nałecz-Jawecki, 2016;Huerta-Fontela et al, 2011). Some data on the occurrence of sartans, and their primary biodegradation products at STPs (such as valsartan acid), in finished tap water have been also published (Giebułtowicz and Nałecz-Jawecki, 2016). However, no information is available neither regarding the variables affecting their half-lives (t1/2) during chemical treatments of polluted waters (as those employed in the production of tap water), nor above the possible formation of transformation products (TPs) during these processes.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, sartans have also polluted the surface water compartment. In rivers impacted by the discharges of STPs, their concentrations stay in the range from 10 to 500 ng L -1 (Giebułtowicz and Nałecz-Jawecki, 2016;Huerta-Fontela et al, 2011;Kasprzyk-Horden et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Sartans are a class of pharmaceuticals employed in the treatment of hypertension (Giebułtowicz et al, 2016;Oosterhuis et al, 2013). Currently, seven drugs from this family are marketed in Europe.…”
Section: Introductionmentioning
confidence: 99%
“…This fact increases significantly their mobility in the aquatic media. Some members of the sartan group are often included in multianalyte methodologies applied to the screening of emerging pollutants in the aquatic environment (Cantwell et al, 2018;Hermes et al, 2018;Nödler et al, 2016), in methods dealing with the analysis of cardiovascular drugs (Giebułtowicz et al, 2016;Stankiewicz et al, 2015), and, less often, in more specific studies restricted to this family of pharmaceuticals (Bayer et al, 2014). From these previous works, it can be concluded that sartans are ubiquitous in raw wastewater, with average concentrations usually above 1000 ng L -1 (Bayer et al, 2014;Stankiewicz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We observed the occurrence of 11 out 98 examined from the following therapeutic groups: antibiotics, sulfonamides, antidepressants, anticonvulsants, antiparasitics, antipsychotics and cardiovascular drugs. The pharmaceuticals were previously detected in Polish surface waters as well [ 37 , 38 , 39 , 40 ]. The highest concentration in fish muscles (>2.0 ng/g) was observed for ofloxacin and thiabendazole.…”
Section: Discussionmentioning
confidence: 99%